Development of the multi-directional ablation process using the femtosecond laser to create a pattern on the lateral side of a 3D microstructure - Cheol Woo Ha; Yong Son (Scientific Reports, 2023)
Abstract Two-photon stereolithography (TPS) is widely used for the fabrication of various three–dimensional (3D) structures with sub-micron fabrication resolution in a single fabrication process. However, TPS is unsuitable for microstructures with fine-hole patterns. The laser ablation process can be easily drilled, or made holes in various materials. However, in the case of laser ablation, the focal plane of the laser is fixed, which is limited to the processing plane. In this study, a multidirectional ablation process is studied to apply laser ablation to various processing planes of a 3D microstructure fabricated by the TPS process. A 3D hybrid fabrication process with the advantages of both TPS and laser ablation is expected to improve the fabrication efficiency. The 3D hybrid process is proposed based on a single laser source. The microstructure is fabricated using TPS, and the multi-directional ablation process creates a hole in the lateral side of the 3D microstructure. To develop the multidirectional ablation process, the reflecting mirror system should be designed to adaptably rotate the laser focal plane and guide the laser path for the target process plane. Through various examples, we demonstrate the ability of the multi-directional ablation process with various examples.